DEVELOPMENT OF A COMPUTATIONAL TOOL FOR EVALUATING TECHNICAL EFFICIENCY BASED ON DEA - Surco, Douglas Fukunaga (2006)
This work describes concepts and models related with the calculation of indexes of technical efficiency and the development of a computational tool for evaluation of the technical efficiency and of the productivity based on DEA (Data Envelopment Analysis). To the all 37 models were implemented, included the measures Complete DEA (measured SBM and RAM) and the Index of Malmquist for evaluation of the productivity. It can be obtained gratuitously in the site: http://www.mat.ufpr.br/~volmir/DEA.html